50‐4: High‐Performance Pyrimidine‐Based TADF Emitters Realizing Pure Blue‐to‐Green Emission with EQE of 25%. Issue 1 (2nd June 2017) - Sasabe, Hisahiro; Komatsu, Ryutaro; Nakao, Kohei; Ohsawa, Tatsuya; Hayasaka, Yuya; Kido, Junji
Abstract : A series of pyrimidine‐based pure blue‐to‐green emitters are developed, and investigated the structure‐property relationships. A pure blue emitter realized a power efficiency of 20 lm W ‐1 at CIE of (0.16, 0.15), and a green emitter exhibited a power efficiency of over 110 lm W ‐1 at CIE of (0.36, 0.58).